How much is a 'pea‐sized amount'? A study of dentifrice dosing by parents in three countries. (December 2013) - Creeth, Jonathan; Bosma, Mary Lynn; Govier, Katherine
Abstract : To provide optimal fluoride effectiveness against caries while minimising risk of negative effects from excessive ingestion from toothbrushing, the fluoride dose delivered at each occasion is critical. This is particularly important for young children, so using a 'pea‐sized amount' is generally recommended. However, there appears little guidance regarding what this means in practice, although it has been indicated to be 0.25 g. This study investigated, using conventional toothpastes and toothbrushes in Germany, the USA and the UK, how much toothpaste parents dispense for their 3‐ to 6 year‐old children, and their interpretation of a 'pea‐sized' amount of toothpaste. When asked to dispense the amount they would normally for their child, the majority of parents dosed substantially more than 0.25 g; in Germany, all parents over‐dispensed. The amount dispensed varied widely: those parents at the 75th centile dispensed approximately twice the amount dispensed by those at the 25th centile, irrespective of country. When asked to dispense a pea‐sized amount, the mean amount dosed decreased significantly in all countries. In the USA, electric toothbrush users dispensed about 0.1 g more than manual toothbrush users. While over‐dispensing of fluoride toothpaste remains a cause for concern, it may be argued that the general recommendation to use a pea‐sized amount of toothpaste generally works well in practice to balance the conflicting demands of risk and benefit from toothbrushing with fluoride toothpaste in young children.